New industrial spaces as sustainable communities: the case of digital incubators - Camilla Costa; Margherita Turvani (European Regional Science Association (ERSA), 2013)
The last decade has been marked by a debate on a ?paradigm shift? of economic and territorial development, in transition toward a new economic and industrial system based on knowledge, ?immateriality? and creativity. Against the background of an increased globalization and industrial restructuring, the links between innovation, creativity and economic practices have invited to a new vision of material and immaterial ?industrial spaces?. This invites to a study of the hard and soft assets and of the relationships that are the constituents of a ?place?, where such potentials can ?materialize?. Elusive and yet pervasive ideas, such as regional competitiveness, creative class, and human capital need to inform planning in order to give shape to communities of innovators, new entrepreneurs, and creative people. In order to investigate this relationship between planning, new industrial spaces and community building, the paper focuses on the experience of H-Farm, a private venture incubator for digital start-ups. The case study shows how new industrial spaces develop building on emerging forms of digital entrepreneurship, and at the same time affecting the patterns of settlement in the territory. We find that, within the activation of territorial planning, the physical and social environment in which the entrepreneurial activity takes place closely influences the generation of creative and innovative thinking.
Keywords: 330; Economic Development; Technological Change; Growth; Development Planning